SPATIAL DISTRIBUTION OF DEUTERIUM IN ATMOSPHERIC WATER VAPOR: DIAGNOSING SOURCES AND THE MIXING OF ATMOSPHERIC MOISTURE - Yamanaka T.; Shimizu R. (My University, 2007)
We measured the stable isotopic composition of hydrogen (δD) within atmospheric water vapor collected simultaneously at six sites in the vicinity of a lake (Lake Kasumigaura, Eastern Japan) to determine its spatial distribution characteristics and thereby diagnose sources and mixing of atmospheric moisture. The measured spatial distribution of δD showed no relation to distance from the lake, although it showed a correlation with the distribution of the water-vapor mixing ratio Q. For two of the three sampling days, we found a simple two-component (i.e., water vapor transpiring from local land surfaces and pre-existing vapor in the background atmosphere) mixing line in a Keeling plot (i.e., δ - 1/Q diagram). On a third day, however, contributions from lake evaporation were detected in addition to the above components. On this day, lake-derived vapor accounted for approximately 10-20% of atmospheric water vapor at the sites located leeward of the lake. The observed differences in mixing patterns among sampling days can be explained by a simple atmospheric moisture budget. Thus, it is likely that simultaneous isotopic measurements of atmospheric water vapor at multiple locations with aid of Keeling plot are capable of giving us useful information in diagnosing the sources and mixing pattern of the vapor. © 2007 Elsevier Ltd. All rights reserved.